Studi sull'edilizia domestica in Calabria dall'età coloniale all'Ellenismo - Casalicchio, Alessandra; De Gaetano, Roberto; Paoletti, Maurizio (My University, 2019)
The research project aims to reconstruct the development of the residential system of the Greek colonies in Calabria from the Colonial age until Hellenism, starting from the study of the Greek house in the motherland – considered from a typological, planimetric and functional point of view – to arrive to its comparisons with some case studies from Magna Graecian and Sicilian poleis and from other Calabrian indigenous centers. The analytical research of the different sites, both in Greece and Calabria, aims to determine the specific characteristics of the single domestic units, trying to reconstruct the cultural models of reference. From a methodological point of view, this study promotes the analysis of the many examples, highlighting the existence of different housing models. The various methodological approaches related to the domestic spaces have been examined, which have been used in Greece, as well as in Magna Graecia and Sicily. A seminal premise to the analysis of the development of the Greek housing model has been the description of the Greek house in the ancient literary sources, which have been used to understand the structural and functional characteristics and the aspects connected to the inner daily activities, in relation to archaeological evidences. Within the regular urban planning of the Greek poleis in Calabria, the housing structures show different typologies, reflecting the needs of the various social classes and of the geographical context. The analysis of the functional aspect of the different rooms is often more useful than the typological one, because it allows to detect a greater complexity in the use of space from the Archaic age to the Hellenism. A further purpose of the research was to analyze an oikos of Medma, the sub-colony of Locri Epizefiri, by considering the different spaces of the house and the archaeological materials, which came from the excavations done in 1978 in Montagnese’s property and that can be dated between the end of the 5th and the beginning of the 3rd century B.C. In addition, the analytical analysis of some Italic sites and case studies of Magna Graecia and Sicily has shown the presence of diversified housing units in a regular urban planning, with variations according to the historical period, the availability of building materials, the territorial morphology and, finally, to the influences from the local housing tradition. The housing of the Greek poleis in Calabria reflects the Greek models, that are often re-elaborated in a more independent way. Moreover, during the life phase of most of the houses we can observe how structural changes modify the primal planimetric framework and the consequential variation of the original reference model and, in some cases, of the surface extent in the housing units.
Dottorato di ricerca internazionale in studi umanistici: Testi, saperi, pratiche dall’antichità classica alla contemporaneità, Ciclo XXXI, a.a. 2018-2019
Keywords: Architettura greca. Calabria